Glass-ceramics fabricated by efficiently utilizing coal gangue - W. Dang (Journal of Asian Ceramic Societies, 2020)
Glass-ceramics with high strength and lightweight were developed by comprehensively utilizing coal gangue and clay. This work optimized the many processing parameters including the rate of using coal gangue, coal gangue to clay ratio, mineralizers, and process of forming and sintering. Using coal gangue of 75% and coal gangue to clay ratio of 3/1 made the mechanical properties optimal. The sintering temperature of 1370 °C was found to be optimal because mullite and spinel become the main crystal phase and thereby realizing high strength, low water absorbance, and low density for the sintered glass-ceramics. The mechanical properties of the glass-ceramics were further enhanced by adding mineralizer (TiO2, ZnO, and MnO2/dolomite) with reasonable amounts. Moreover, the properties were enhanced by optimizing processing parameters. We developed an excellent approach to sinter glass-ceramics illustrated high strength, lightweight, and low water absorption by efficiently utilizing and managing waste minerals. The sintered glass-ceramics can be used as high-performance proppant materials, cooking ceramics, and building materials